Updates in Osteoarthritis - Vinall, Maria (MD Conference Express, 2006)
This article discusses the clinical markers for osteoarthritis (OA), a study looking at the relationship between changes in bone marrow edema (BME) and clinical features in patients with OA, joint distraction treatment for OA, pharmacological approaches to OA treatment, as well as EULAR 2006 recommendations for the management of hand OA, among other things.